Anterior Cingulate Engagement in a Foraging Context Reflects Choice Difficulty, Not Foraging Value - Shenhav, Amitai (2014)
Previous theories predict that human dorsal anterior cingulate (dACC) should respond to decision difficulty. An alternative theory has been recently advanced which proposes that dACC evolved to represent the value of “non-default,” foraging behavior, calling into question its role in choice difficulty. However, this new theory does not take into account that choosing whether or not to pursue foraging-like behavior can also be more difficult than simply resorting to a “default.” The results of two neuroimaging experiments show that dACC is only associated with foraging value when foraging value is confounded with choice difficulty; when the two are dissociated, dACC engagement is only explained by choice difficulty, and not the value of foraging. In addition to refuting this new theory, our studies help to formalize a fundamental connection between choice difficulty and foraging-like decisions, while also prescribing a solution for a common pitfall in studies of reward-based decision making.